2015
DOI: 10.1152/ajplung.00242.2014
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Akt1, but not Akt2, attenuates the development of pulmonary hypertension

Abstract: Pulmonary vascular remodeling, mainly attributable to enhanced pulmonary arterial smooth muscle cell proliferation and migration, is a major cause for elevated pulmonary vascular resistance and pulmonary arterial pressure in patients with pulmonary hypertension. The signaling cascade through Akt, comprised of three isoforms (Akt1-3) with distinct but overlapping functions, is involved in regulating cell proliferation and migration. This study aims to investigate whether the Akt/mammalian target of rapamycin (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 78 publications
(93 reference statements)
7
82
1
Order By: Relevance
“…Indeed, we detected significantly higher Yap/Taz protein levels, activity ( components to the pulmonary hypertension (PH) network (27) (see Figure E6) from which the AKT set was ranked as a most probable candidate. A proliferative/antiapoptotic role of mTORAkt and Notch3 intracellular domain in PAH PAVSMCs had been reported by us and others (5,28,29), and we confirmed activation of HIF1 and Wnt/b-catenin using respective activation assays (see Figure E7). Supporting the bioinformatic predictions, inactivation of LATS1 in nondiseased human PAVSMCs significantly up-regulated mTOR-Akt, as evidenced by increase in P-S473 Akt, mTORC2-specific P-T2481 mTOR, and mTORC1-specific P-S6 (5,14,(30)(31)(32), and led to accumulation of b-catenin, Notch3 intracellular domain, and HIF1a, whereas "restoration" of P-T1079 LATS1 or suppression of Yap in PAH PAVSMCs by LATS1 T1079D or VP had the opposite effect ( Figure 3; see Figure E8).…”
Section: Hippo/lats1 Inactivation Promotes Human Pah Pavsmc Proliferasupporting
confidence: 89%
“…Indeed, we detected significantly higher Yap/Taz protein levels, activity ( components to the pulmonary hypertension (PH) network (27) (see Figure E6) from which the AKT set was ranked as a most probable candidate. A proliferative/antiapoptotic role of mTORAkt and Notch3 intracellular domain in PAH PAVSMCs had been reported by us and others (5,28,29), and we confirmed activation of HIF1 and Wnt/b-catenin using respective activation assays (see Figure E7). Supporting the bioinformatic predictions, inactivation of LATS1 in nondiseased human PAVSMCs significantly up-regulated mTOR-Akt, as evidenced by increase in P-S473 Akt, mTORC2-specific P-T2481 mTOR, and mTORC1-specific P-S6 (5,14,(30)(31)(32), and led to accumulation of b-catenin, Notch3 intracellular domain, and HIF1a, whereas "restoration" of P-T1079 LATS1 or suppression of Yap in PAH PAVSMCs by LATS1 T1079D or VP had the opposite effect ( Figure 3; see Figure E8).…”
Section: Hippo/lats1 Inactivation Promotes Human Pah Pavsmc Proliferasupporting
confidence: 89%
“…Resveratrol inhibited hypoxia-induced arginase activity as well as proliferation in human PASMCs (39) and in vivo resveratrol treatment attenuated the development of hypoxia-induced RVH in rats. The effect of resveratrol upon arginase II was mediated via inhibition of the PI3K-Akt signaling pathway, findings consistent with other recent reports demonstrating a role for Akt signaling in PASMC proliferation in response to hypoxia (233). The Akt family contains three isoforms, and the use of mice with deficiency for Akt1 or Akt2 revealed that loss of Akt1 prevented hypoxia-induced proliferation in vitro and development of hypoxia-induced PH.…”
Section: Pathways and Targetssupporting
confidence: 90%
“…Thus, we could also speculate that miR-223 downregulation can also lead to increased KLF5 expression observed in PAH (8). Moreover, downstream miR-223 targets IGF-1R and HSP90␤ seem to act on proliferation through the phosphatidylinositol 3-kinase, Akt, and mammalian target of rapamycin (PI3K/Akt/ mTOR) pathway (13,18) known to play a role in PAH pathophysiology (10,26,36).…”
Section: Discussionmentioning
confidence: 99%